2016
DOI: 10.3390/ma9040224
|View full text |Cite
|
Sign up to set email alerts
|

Application of Image Analysis to Identify Quartz Grains in Heavy Aggregates Susceptible to ASR in Radiation Shielding Concrete

Abstract: Alkali-silica reaction (ASR) is considered as a potential aging-related degradation phenomenon that might impair the durability of concrete in nuclear containments. The objective of this paper is the application of digital analysis of microscopic images to identify the content and size of quartz grains in heavy mineral aggregates. The range of investigation covered magnetite and hematite aggregates, known as good absorbers of gamma radiation. Image acquisition was performed using thin sections observed in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…[16] showed that almost 90% of all cases with ASR-damaged concrete structures were caused by porous opaline or calcareous opaline flint in the sand fraction. Jóźwiak-Niedźwiedzka et al [17] also confirmed the effectiveness of image analysis to assess the potential for ASR in aggregate. Mortar-bars after accelerated tests were observed on SEM with EDS.…”
Section: Resultsmentioning
confidence: 72%
“…[16] showed that almost 90% of all cases with ASR-damaged concrete structures were caused by porous opaline or calcareous opaline flint in the sand fraction. Jóźwiak-Niedźwiedzka et al [17] also confirmed the effectiveness of image analysis to assess the potential for ASR in aggregate. Mortar-bars after accelerated tests were observed on SEM with EDS.…”
Section: Resultsmentioning
confidence: 72%
“…Depending on the mean crystal size, the reactive forms of quartz were classified: highly-reactive quartz: <10 μm, reactive quartz: 10–60 μm, uncertain quartz: 60–130 μm, and harmless quartz: >130 μm. A description of the subsequent stages of the individual phases analysis is provided in Jóźwiak-Niedźwiedzka et al [25].…”
Section: Methodsmentioning
confidence: 99%
“…Thin section image acquisition was performed using an Olympus BX51 microscope in cross-polarized light (XPL) with λ plate. The λ plate is a first-order red plate which consists of a quartz or gypsum plate that is cut parallel to the optic axis, about 62 μm thick, which shows a first-order red interference color in diagonal position [8].…”
Section: Testing Methods-the Microstructure Analysismentioning
confidence: 99%